PENGARUH DEWAN KOMISARIS, EFEKTIVITAS KOMITE AUDIT, KEPEMILIKAN INSTITUSIONAL, PERTUMBUHAN PERUSAHAAN, DAN PENDANAAN EKSTERNAL, TERHADAP PEMILIHAN AUDITOR EKSTERNAL (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 201 - Tantri Rohmani, 12.05.52.0100; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2016)
The aim of the study is to examinethe effect of board of commissioners, the effectivivess of audit, the institusional ownership, the company growth, and the external financing of the election for external auditors on the manufacturing companies that go public in Indonesia.The population in this research are companies that includes in the manufacturing sector which is registered in the Indonesia Stock Exchange (BEI) in 2012-2014. The sample salected are 138 companies that using purposive sampling technique. The analysis technique used logistic regression.The research results showedboard of commissioners, the effectivivess of audit, and the external financing effect to the selection of the external auditor. The institusional ownership, the company growthdo not significant effect to selectionof the external auditor.Keywords: Board of Commissioners, the effectivivess of audit, the institusional ownership, the company growth, and the external financing of the election for external auditors.